2010
DOI: 10.1002/eji.200939527
|View full text |Cite
|
Sign up to set email alerts
|

Human rhinoviruses induce IL‐35‐producing Treg via induction of B7‐H1 (CD274) and sialoadhesin (CD169) on DC

Abstract: IL-35 is a heterodimer of EBV-induced gene 3 and of the p35 subunit of IL-12, and recently identified as an inhibitory cytokine produced by natural Treg in mice, but not in humans.Here we demonstrate that DC activated by human rhinoviruses (R-DC) induce IL-35 production and release, as well as a suppressor function in CD4 1 and CD8 1 T cells derived from human peripheral blood but not in naïve T cells from cord blood. The induction of IL-35-producing T cells by R-DC was FOXP3-independent, but blocking of B7-H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 37 publications
1
52
0
1
Order By: Relevance
“…Taking into account IL-35 is expressed in human regulatory T cells (Tregs) (Pflanz et al, 2006), it is deemed to characteristics of Treg cells. Previous study found IL-35 inhibit advancement of inflammatory diseases by suppressing the activity of effector T cells such as Th2 and Th17 (Collison et al, 2007;Collison et al, 2010;Kochetkova et al, 2010;Seyerl et al, 2010;Huang et al, 2011;Whitehead et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Taking into account IL-35 is expressed in human regulatory T cells (Tregs) (Pflanz et al, 2006), it is deemed to characteristics of Treg cells. Previous study found IL-35 inhibit advancement of inflammatory diseases by suppressing the activity of effector T cells such as Th2 and Th17 (Collison et al, 2007;Collison et al, 2010;Kochetkova et al, 2010;Seyerl et al, 2010;Huang et al, 2011;Whitehead et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…IL-35 expression has been thought to be specific to Tregs, because EBI3 is a downstream target of Foxp3 (35). However, according to recent reports, EBI3 is also expressed in other cell types, including intestinal epithelium and aortic smooth muscle cells (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…IL-35-mediated tumor immunosuppression IL-35 is a heterodimeric cytokine belonging to the IL-12 family, consisting of the Epstein-Barr virus-induced gene-3 and IL-12p35 subunits. IL-35 is highly expressed by mouse FOXP3 + Treg cells (Collison et al, 2007) and stimulated human Treg cells (Chaturvedi et al, 2011;Seyerl et al, 2011). There are contradictory reports regarding the role of IL-35.…”
Section: Cd28mentioning
confidence: 99%